BIOEQUIVALENCE STUDY OF GENERIC MOLNUPIRAVIR IN HEALTHY VOLUNTEERS - V. B. Vasilyuk; A. Yu. Boroduleva; P. D. Sobolev; A. G. Nikiforova; V. G. Mozgovaya; O. V. Filon; A. V. Zinkovskaya; V. G. Ignatiev; M. Yu. Samsonov; I. S. Kozlova; E. K. Khanonina (Фармация и фармакология (Пятигорск))
Molnupiravir is one of the drugs for the etiotropic therapy of a new coronavirus infection COVID-19. It has confirmed its clinical efficacy in the treatment of patients with mild and moderate COVID-19, including those who are at high risk of progressing to severe disease.The aim of the study was to evaluate bioequivalence of the generic drug molnupiravir ALARIO-TL and the original drug Lagevrio with a single oral administration in healthy volunteers.Materials and methods. This bioequivalence study was an open, randomized, two-period crossover study. In each of the two periods, volunteers received a single dose of the test drug, or reference drug molnupiravir, in the form of capsules at the dose of 200 mg. The washout period between the doses was 3 days. To determine pharmacokinetic (PK) parameters and bioequivalence, the concentration the concentration of N-hydrozycytidine (NHC), the main molnupiravir metabolit in the blood plasma of volunteers was evaluated. The blood plasma sampling was carried out in the range from 0 to 16 hours in each of the study periods. Bioequivalence was assessed by comparing 90% confidence intervals (CIs) for the ratio of geometric means of AUC(0–16) and Cmax of the test drug and reference drugs with the established equivalence limits of 80.00 – 125.00%.Results. A total of 28 healthy male volunteers were included in the study. According to the results of the statistical analysis, after the administration of the test and reference drugs, the 90% CIs for the ratio of the geometric means of AUC (0–16) and Cmax were 96.31% – 113.64% and 91.37% – 114.8%, respectively. These intervals fit within the established limits of 80.00–125.00%, which confirms the bioequivalence of the drugs. When comparing the frequency of the individual adverse events registration, no significant differences were found out after the administration of the test and reference drugs.Conclusion. Based on the results of this study, it can be concluded that the test and reference drugs of molnupiravir are bioequivalent. In addition, the data obtained indicate that the drugs have similar safety profiles.